A 3D-honeycomb-like catalyst: a nitrogen-doped carbon material with cobalt and manganese-oxide for C–H bond oxidation. Issue 11 (7th October 2019) - Wang, Kaizhi; Zhao, Shiling; Ma, Lei; Yang, Ming; Qin, Jiaheng; Huang, Xiaokang; Gong, Li; Xiong, Yucong; Li, Rong
Abstract : A three dimensional mesoporous honeycomb-like material that is multifunctional and easily recoverable, and shows efficient performance is described. Abstract : A three dimensional mesoporous honeycomb-like material that is multifunctional and easily recoverable, and shows is described. This material is used in the oxidation of C–H bonds by tert -butyl hydroperoxide (TBHP) to form ketones, aldehydes, amides, and nitriles. The effects of temperature, amount of catalyst, reaction time, and oxidant on the selective oxidation of ethylbenzene were investigated. Under economical, environmentally efficient, and sustainable reaction conditions, the yields of most substrates reached more than 90% at 50 °C for 6 h. Transmission electron microscopy (TEM), X-ray diffraction (XRD), thermal gravimetric analysis (TGA), and Raman, Fourier transform-infrared (FT-IR), and X-ray photoelectron spectroscopy (XPS) were used for the characterization of the pre-catalyst.